2005
DOI: 10.1108/02630800510586907
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting construction labour productivity for Malaysian residential projects

Abstract: PurposeConstruction labour productivity is of great interest to practitioners and researchers because it affects project cost and time overrun. This paper evaluates and ranks the importance, frequency and severity of project delay factors that affect the construction labour productivity for Malaysian residential projects.Design/methodology/approachA total of 100 respondents consisting of 70 contractors, 11 developers and 19 consultants participated in this study. The respondents were asked to indicate how impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(79 citation statements)
references
References 6 publications
7
69
0
3
Order By: Relevance
“…This is a great concern as the financial vulnerability of the public organisations could cascade as an impact towards private organisations. Abdul-Kadir et al (2005) highlighted the detrimental effects of such late payment which had resulted in suppliers not getting paid on time by the contractors, causing frequent disruptions in material acquisition and the loss of trust by the suppliers to the contractors. Hence despite the private organisations' good financial strength, it does not guarantee that the organisations can overcome the effect of under payment or late payment by the public organisations due to this cascading impact from a different supply chain.…”
Section: Liquidity or Credit Vulnerabilitymentioning
confidence: 99%
“…This is a great concern as the financial vulnerability of the public organisations could cascade as an impact towards private organisations. Abdul-Kadir et al (2005) highlighted the detrimental effects of such late payment which had resulted in suppliers not getting paid on time by the contractors, causing frequent disruptions in material acquisition and the loss of trust by the suppliers to the contractors. Hence despite the private organisations' good financial strength, it does not guarantee that the organisations can overcome the effect of under payment or late payment by the public organisations due to this cascading impact from a different supply chain.…”
Section: Liquidity or Credit Vulnerabilitymentioning
confidence: 99%
“…This result was supported by (Thomas and Sakarcan 1994) who found that supervision and proper coordination of subcontractors have the most significant impact on on-site labour productivity. (Abdul Kadir et al 2005) put emphasize on coordination with subcontractors, which was ranked as one of the influential factors in the study. Furthermore Jergeas (2009) and KPMG (2009) argue that effective project integration management, comprising the activities that integrate, coordinate and bring together the various functions and multiple stakeholders, is the key to achieving onsite productivity and performance.…”
Section: Project Management/project Team Characteristicsmentioning
confidence: 99%
“…Artículos Incumplimiento y problemas en [2], [7], [16], [15] [17] general con subcontratistas Calamidades climáticas [16], [18], [19] Condiciones gubernamentales [16] Cambios en el alcance del [5], [7], [9], [18], [20] contrato por parte del dueño Escasez de trabajadores [9], [18], [21] Mano de obra no calificada [1], [7], [9], [18], [19], [20] Mala planeación y programación [2], [3], [5], [6], [7], [9], [11], [12], [17], [20], [22] por parte del contratista Falta de comunicación entre las [5], [17] diferentes partes involucradas en los proyectos. Fluctuaciones de la moneda [1] Cambios en los diseños [11], [12], [18], [19], [23] Conflictos laborales y huelgas [17], [18] En India, por ejemplo, se encontró que en promedio, entre una muestra de 290 proyectos, existía una excedencia en costos del 73 % [5].…”
Section: Factorunclassified
“…En la Tabla 2 se muestra un resumen de las principales causas que influyen en costo. [13], [15], [18], [21] contrato por parte del dueño Esta investigación se realizó teniendo en cuenta que las diferencias en tiempos y costos en proyectos de construcción se presentan constantemente en el país, lo que constituye una constante preocupación por parte de los desarrolladores de proyectos. Así mismo, en el país es escasa la literatura reportada que analice el tema, por lo que contar con información que permita identificar los factores más relevantes que generan diferencias de tiempos y costos en proyectos de construcción y poder así determinar acciones de mejora.…”
Section: Factorunclassified